Antibody profiles for the diagnosis of antiphospholipid syndrome - Pengo, Vittorio; Biasiolo, Alessandra; Pegoraro, Cinzia; Cucchini, Umberto; Noventa, Franco; Iliceto, Sabino (Thrombosis and Haemostasis, 2005)
Among the so called‘antiphospholipid antibodies’, the presence of Lupus Anticoagulant (LA) is associated with thrombosis-related events and defines the antiphospholipid syndrome. The role of anti-cardiolipin (aCL) antibodies and anti-human β2-glycoprotein I (aβ2GPI) antibodies is less striking. Since the problem of standardization for these tests is far from resolved, we evaluated whether the combination of results (antiphospholipid laboratory profiles) could help to better classify these patients. Over a 6-year period, 618 consecutive subjects (55% of whom had previous documented thrombosis-related events) were referred to our clinic for Antiphospholipid antibody detection. LA was detected according to internationally accepted recommendations. ACL and aβ2GPI antibodies were detected by Enzyme-Linked-Immunosorbent Assay (ELISA). Patients’ records were reviewed for the presence of previous thromboembolic events or obstetric complications according to Sapporo’s clinical criteria for the diagnosis of antiphospholipid syndrome (APS) and each patient underwent a physical examination. When individual tests were considered in a multivariate analysis which took into account age, gender, the presence of SLE or other autoimmune diseases and established risk factors for venous and arterial thromboembolism, LA (Odds Ratio 4.4, Confidence Interval 1.5–13.3) and aβ2GPI antibodies (Odds Ratio 2.9, Confidence Interval 1.1–7.5) but not aCL antibodies (Odds Ratio 1.2, Confidence Interval 0.5–2.7) were found to be independent risk factors for thrombosis-related events. When antiphospholipid antibody profiles instead of individual test positivity were analyzed in the above mentioned model, triple positivity resulted a strong independent risk factor (Odds Ratio 33.3, Confidence Interval 7.0–157.6), retaining its significance when the association with venous or arterial thromboembolism was considered. Double positivity with negative LA was close to significance for thrombosis-related events (Odds Ratio 2.2, Confidence Interval1.0–5.2, p=0.056) and highly significant risk factor for obstetric complications (Odds Ratio 10.8, Confidence Interval 2.9–40.8). Other combinations did not reach statistical significance. The mean level of IgG aβ2GPI antibodies was statistically higher in triple positive profile and might account for positive LA. As compared to a single test, the analysis of a complete antiphospholipid antibody profile can better determine patients at risk.
Keywords: Phospholipids; syndrome; lupus anticoagulant; β2-glycoprotein I